Pengaruh Periklanan Dan Personal Selling Terhadap Pengambilan Keputusan Mahasiswa Memilih Organisasi PMII (Pada Rayon Al-Farabi Fakultas Ekonomi Dan Bisnis Universitas Islam Malang 2019) - Ach Bilhaq Nazal; Muhammad Mansur; M. Khoirul ABS (UNIVERSITAS ISLAM MALANG, 2020)
ABSTRACTStudents are confronted with many choices of qualified organizations also have their respective advantages. No exception on the Malang Islamic University Campus, Malang Islamic University does have three extra-campus organizations, namely PMII, HMI and GMNI. However, Malang Islamic University is the largest PMII regeneration barn in Malang. Reasons for Malang Islamic University to become the largest PMII regeneration barn in Malang because this campus is an NU campus and of course PMII is an organization based on Ahlusunnah wal Jama'ah and PMII is one of the student organizations formed to supply young intellectuals In this study there are two functions variable is the dependent variable (independent) and the independent variable (dependent). Dependent variables are variables that are influenced or explained by independent variables, while independent variables are variables that can affect other variables. Where this research is a study of primary data through a questionnaire. The data used are secondary data and primary data. The statistical method used is multiple linear regression by conducting classical assumption tests, correlation coefficients and determination coefficients and testing hypotheses namely f test and t test.The results of the research conducted that the advertisement variables influence the decision making of students choosing the PMII organization (Rayon Al-Farabi FEB Unisma) and the personal selling variable influences the students' decision making in choosing the PMII organization (Rayon Al-Farabi FEB Unisma). The results of this study can provide information to rayon administrators about the influence of advertising and personal selling on the management of rayon AL-Farabi and also for further researchers so that they can add other variables that can influence student decision making that are not examined by researchers.Keywords: Advertising; Personal Selling